Manajeman Bimbingan dan Konseling Dalam Meningkatkan Mutu Pendidikan - Pasaribu, Putri Dirgahayu; Nasution, Inom; Anggraini, Nurdelita; As Syifa, Salsabila; Harahap, Mahyuni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Guidance and Counseling Management is very important in improving the quality of education by providing the support and intervention that students need to reach their maximum potential. In an effort to improve the quality of education, BK management must also be oriented towards customer satisfaction, namely students and parents. BK management must be able to provide very high satisfaction to customers by improving the quality of BK services and increasing student participation in the learning process. This article examines how the implementation of effective BK management can improve the quality of education through strengthening learning motivation, improving student behavior, and reducing the level of delinquency. teenager. Through literature study, it involves theoretical studies. The research results show that good guidance and counseling management contributes significantly in shaping students' character and academic achievement, thus emphasizing the importance of integrating guidance and counseling in strategies to improve the quality of education.